Clinical Characteristics in a Sample of Transsexual People - Maria Rita Lerri; Adriana Peterson Mariano Salata Romão; Manoel Antônio dos Santos; Alain Giami; Rui Alberto Ferriani; Lúcia Alves da Silva Lara (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose To assess the clinical characteristics of subjects with gender dysphoria (GD). Method A cross-sectional study of adults with GD. Symptoms of anxiety and depression were measured using the Hospital Anxiety and Depression Scale (HADS). Sociodemographic data, clinical data and life habits were recorded. Results Total of 44 subjects participated in the study: 36 (82%) trans women and 8 (18%) trans men. Forty-three (98%) of the GD patients had anxiety (36 [100%] trans women and 7 [87.5%] trans men), and 36 (82%) had depression (29 [80.5%] trans women and 7 [87.5%] trans men). Suicide had been attempted by 32 (73%) subjects. The rates of depression were lower among the subjects living with partners, parents, or other people than among those living alone (p = 0.03), and it was also lower among the subjects who were married compared to those who were dating or single (p = 0.03). Conclusion Improving the relationship status may reduce the prevalence of depressive symptoms in GD patients. There was a high rate of attempted suicide in this sample.